A framework for soil-water modeling using the pedostructure and Structural Representative Elementary Volume (SREV) concepts - Braudeau, Erik F.; Mohtar, Rabi H. (Frontiers in Environmental Science, 2014)
Current soil water models do not take into account the internal organization of the soil medium and consequently ignore the physical interaction between the water film at the surface of solids that form the soil structure and the structure itself. In this sense, current models deal empirically with the physical soil properties, which are all generated from this soil water and soil structure interaction. As a result, the thermodynamic state of the soil water medium, which constitutes the local physical conditions of development for all biological and geochemical processes within the soil medium, is still not well defined and characterized. This situation limits modeling and coupling the different processes in the soil medium since they all thermodynamically linked to the soil water cycle. The objective of this article is to present a complete framework for characterizing and modeling the internal soil organization and its hydrostructural properties resulting from interaction of its structure with the soil water dynamics. The paper builds on the pedostructure concept, which allowed the integration of the soil structure into equations of water equilibrium and movement in soils. The paper completes the earlier framework by introducing notions of soil-water thermodynamics that were developed in application to the concept of the Structural Representative Elementary Volume (SREV). Simulation of drainage after infiltration in the Yolo loam soil profile, as compared to measured moisture profile using the measured soil characteristic parameters, showed a high degree of agreement. This new modeling framework opens up new prospects in coupling agro-environmental models with the soil medium, recognizing that the soil organization, hydro-structural, and thermodynamic properties are the foundation for such coupling.